The Influence of Organizational Culture, Self-Confidence, and Gender on Employee Performance with Employee Involvement as a Mediator - Jamika, Dodik; Nurdin, Muhammad (Universitas Dharma Wacana, 2025)
This study investigates the impact of organizational culture, self-confidence, and gender on employee performance, with employee engagement serving as a mediating variable. The research employs a quantitative approach, collecting data through questionnaires distributed to employees of financing companies registered with the Financial Services Authority (OJK) in Purwakarta Regency, resulting in a sample of 257 respondents. Path analysis is used to examine the direct and indirect relationships between variables. The findings reveal that organizational culture has a significant positive impact on both employee performance and employee engagement. A robust organizational culture fosters a supportive work environment, enhancing motivation, a sense of community, and engagement through effective communication and shared positive values. Self-confidence also positively influences employee performance; however, it does not directly affect employee engagement, highlighting the role of other factors like organizational culture and workplace relationships. Gender positively impacts both performance and engagement, showcasing the benefits of diverse perspectives, collaboration, and inclusivity in the workplace. Furthermore, employee engagement significantly enhances employee performance, as emotionally and professionally engaged employees tend to perform at higher levels. As a mediating variable, employee engagement strengthens the influence of organizational culture, self-confidence, and gender on employee performance, underscoring the critical role of fostering diversity, motivation, and workplace support to drive better outcomes.